Fighting songs and warring words : popular lyrics of two world wars - Murdoch, Brian, 1944- (Routledge, 1990)
The accepted canon of war poetry usually includes only those underlining patriotic or nationalistic views. This study opens up the view of war poetry with the inclusion of such material as Nazi poetry and song, and the poetry of the atomic bomb.